(untitled) (The Shivapuri Journal, 2024)
This article explores the road to and implications of the Russo-Ukraine and the Hamas-Israel wars as the consequences of a rapidly transforming great power politics, transitioning from unipolarity to multipolarity. Drawing from scholarly perspectives and open-source resources, the effort has been to give an outlook extending beyond the wars themselves. The focus is on exploring the potential repercussions of this geopolitical shift the world over, but more importantly for a small country like Nepal. A bifocal lens of that of John J. Mearsheimer’s realist approach and that of Graham Allison’s Thucydides Trap is used to gauge Iinto the state of affairs of Eastern Europe and the Middle East to highlight the examples of such consequences. The conclusion extrapolates the conspicuous duality in the relationship between the great powers- The United States, China, and Russia and analyzes its potential implications for Nepal, drawing insights from the consequences of the Russo-Ukraine and Hamas-Israel wars.